The Bug‐Network ( BugNet ): A Global Experimental Network Testing the Effects of Invertebrate Herbivores and Fungal Pathogens on Plant Communities and Ecosystem Function in Open Ecosystems - Kempel, Anne (2025)
Plants are consumed by a variety of organisms, including herbivores and pathogens, which significantly impact plant biomass, diversity, community composition, and ecosystem functioning. While the impacts of vertebrate herbivores are well established, the effects of consumer groups such as insect herbivores, mollusks, and fungal pathogens on plant communities are less clear and remain understudied in many systems. Existing evidence of how they affect plant biomass, diversity, and community composition is mixed, and most studies have focused on individual consumer groups in isolation. However, different consumer groups interact with each other, directly or indirectly, in ways that alter their impacts on plants, and the consequences of these interactions for plant community structure and ecosystem function remain understudied. Further, consumer impacts vary across environmental gradients and likely depend on abiotic conditions such as climate, soil type, or elevation, and biotic conditions such as plant productivity, diversity, or community composition. Existing studies testing the impacts of invertebrate herbivores and fungal pathogens on plant communities differ substantially in methodology, making generalities across large scales difficult. This calls for experimental approaches that implement standardized protocols across many sites. Here, we introduce and report on the methodology of a novel global research network, The Bug-Network (BugNet), that implements standardized consumer-reduction experiments across 5 continents and 18 countries in diverse, herbaceous- or shrub-dominated ecosystems to investigate: (1) the influence of fungal pathogens, insect herbivores, and mollusks on plant diversity and ecosystem functioning, (2) interactions among these consumer groups, and (3) the abiotic and biotic drivers of context-dependent consumer impacts. BugNet aims to advance a predictive understanding of plant-consumer interactions in order to test fundamental ecological hypotheses and improve predictions of global change impacts on biodiversity and ecosystem functioning.